1999
DOI: 10.1016/s0014-5793(99)00438-x
|View full text |Cite
|
Sign up to set email alerts
|

Heparin down‐regulates the phorbol ester‐induced protein kinase C gene expression in human endothelial cells: enzyme‐mediated autoregulation of protein kinase C‐α and ‐δ genes1

Abstract: Overexpression of protein kinase C-K K and protein kinase C-N N has been shown to modulate a number of biological effects, including the cell growth and differentiation. We hypothesized that heparin, a potent antimitogenic drug, could affect the cell proliferation by inhibiting the expression of specific protein kinase C genes. Heparin, markedly but not completely, inhibited the serum-stimulated protein kinase C-K K and -N N mRNA expression. Protein kinase C inhibition or downregulation significantly decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…In this context, PKC down-regulation induced by phorbol esters is caused by proteolytic degradation of the strikingly activated enzyme (Junoy et al, 2002). In turn, moderate PKC activation would result in elevated protein levels (Pintus et al, 1999), which are not masked by proteolysis.…”
Section: To Activate P21mentioning
confidence: 99%
“…In this context, PKC down-regulation induced by phorbol esters is caused by proteolytic degradation of the strikingly activated enzyme (Junoy et al, 2002). In turn, moderate PKC activation would result in elevated protein levels (Pintus et al, 1999), which are not masked by proteolysis.…”
Section: To Activate P21mentioning
confidence: 99%
“…Serum‐starved or growing ECV304 cells cultured in T25 culture flasks (Falcon, Oxnard, CA, USA), were treated as described in figure legends. At the indicated time points, total RNA was extracted, reverse transcribed and amplified according to a previously described procedure [19]. Total RNA (1 µg) from ECV304 cells was reverse‐transcribed for 45 min at 37 °C.…”
Section: Determination Of C‐myc Gene Expression By Rt‐pcr Analysismentioning
confidence: 99%
“…Using 30 PCR cycles, the products of glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH) and c‐ myc amplification were all within the linear phase of the reaction. Indeed, similar conditions have been previously reported for semiquantitative analysis of gene expression [19]. The position of PCR fragments was evaluated by comparison with a DNA molecular mass marker (Gibco BRL).…”
Section: Determination Of C‐myc Gene Expression By Rt‐pcr Analysismentioning
confidence: 99%
“…This difference may be caused by the inhibition of PKCα activation by heparin. Several studies reported that heparin suppresses the activity of PKCα when it is added into not only cells but also cell extracts [14][15][16]. 2.…”
Section: Resultsmentioning
confidence: 99%